2022
DOI: 10.3390/ijerph192416495
|View full text |Cite
|
Sign up to set email alerts
|

The Ecotoxicology of Microbial Insecticides and Their Toxins in Genetically Modified Crops: An Overview

Abstract: The use of microbial insecticides and their toxins in biological control and transgenic plants has increased their presence in the environment. Although they are natural products, the main concerns are related to the potential impacts on the environment and human health. Several assays have been performed worldwide to investigate the toxicity or adverse effects of these microbial products or their individual toxins. This overview examines the published data concerning the knowledge obtained about the ecotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 66 publications
(67 reference statements)
1
0
0
Order By: Relevance
“…Therefore, all results fell within the normal range, and no biologically significant differences were found among the experimental groups. These findings were consistent with those of previous studies by RM Darwish et al, [ 51 ], EC Oliveria-Filho et al, [ 52 ] and MN Haque et al [ 53 ], which also demonstrated no adverse effects on fish fed with genetically modified (GM) algae. It is worth noting that there is a well-established history of the safe consumption of Bt proteins, such as Cryl1Ba.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, all results fell within the normal range, and no biologically significant differences were found among the experimental groups. These findings were consistent with those of previous studies by RM Darwish et al, [ 51 ], EC Oliveria-Filho et al, [ 52 ] and MN Haque et al [ 53 ], which also demonstrated no adverse effects on fish fed with genetically modified (GM) algae. It is worth noting that there is a well-established history of the safe consumption of Bt proteins, such as Cryl1Ba.…”
Section: Discussionsupporting
confidence: 93%